Mitigating the Risk of Prosecutiontermination Based on Restorative Justice from Transactional Aspects - R. Muhamad Ibnu Mazjah (Riviera Publishing, 2024)
Restorative justice, as a manifestation of the Prosecutor's authority and discretion in controlling criminal cases, is vulnerable to abuse of authority if it is not supported by the principle of accountability and a robust supervision system. This research aims to strengthen the authority of prosecutors in applying restorative justice by strengthening regulations at the legal level and proposing stricter criteria for crimes that fall into this category. The research method used is normative legal research, which aims to find coherence between the Prosecutor's authority and legal norms, legal concepts, and legal principles through a legislative and conceptual approach. This study finds that implementing restorative justice by prosecutors requires strengthening regulations and a more muscular supervision system to prevent abuse of authority and ensure legal certainty and justice for all parties. This study implies the need for more transparent regulations and a strict monitoring system to avoid abuse of authority in the application of restorative justice by prosecutors, ensure an accountable law enforcement system, and protect human rights.